Potential role of ICT development and foreign direct investment inflows as drivers for sustainable economic growth: evidence from China and Malaysia / Muhammad Aiman Haziq Norehan - Norehan, Muhammad Aiman Haziq (2022)
Sustainable Economic Growth (SEG) is one of the goals under Sustainable Development Goals (SDG). In order to achieve SEG, China and Malaysia need to have a better FDI inflows and economic growth with a support of ICT development. This study have try to look whether three different models which is FDI inflows, ICT development and economic growth can play importance roles among them in order to support China and Malaysia achieve SEG. This study use time series data with annual data for period 37 years from 1980 to 2017. All the data are collected from World Development Indicators (WDI). All the three proposed model are analyzed by using Autoregressive Distributed Lag (ARDL) estimation technique. The first research objective focused on testing the selected macroeconomic variables for FDI inflows. The result revealed ICT development and labour had significant impact on FDI inflows in China and inflation rate significantly influence FDI inflows in China and Malaysia. The second research objective highlight the impact of selected macroeconomic variables towards ICT development. It was revealed that economic growth and FDI inflows significantly influence ICT development in China; capital significantly influence in China and Malayia and lastly human capital significantly influence ICT development in Malaysia. The third research objective focused on testing the impact of FDI inflows and ICT development toward economic growth in China and Malaysia. The outcome revealed ICT development positively influence economic growth in China; capital and labour significantly impact economic growth in China and Malaysia. This study expected to provide new perspective for many stakeholders and the governments to formulate policies to achieve SEG. In addition, this study can help governments and industry strengthen some important areas in ICT development and FDI inflows in achieving SEG.